A green and degradable mud flocculant and preparation method thereof
By combining photocatalytic degradation of nanomaterials and modified graphene oxide to form cationic nanomaterials, the problem of difficulty in degradation of traditional flocculants and easy agglomeration of nanomaterials is solved, and efficient flocculation and environmentally friendly slurry treatment is achieved.
Patent Information
- Application Number
- CN202411554462.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-04
AI Technical Summary
Traditional polyacrylamide flocculants are difficult to completely degrade after use, resulting in environmental pollution, and graphene oxide and titanium dioxide nanomaterials are prone to agglomeration, affecting the flocculation effect.
Photocatalytic degradation of nanomaterials combined with modified graphene oxide, through vinyl trimethoxysilane, 4-acetyl-2-allylphenol, acryloyloxyethyltrimethylammonium chloride and 1-amine ethyl Chemical substances such as base-3-methylimidazole bromine salt form cationic nanomaterials, enhance the flocculation effect and achieve the degradation of polyacrylamide under light.
It realizes effective degradation of polyacrylamide under light conditions, improves the flocculation effect and material dispersion, reduces environmental pollution, and is suitable for mud-water shield engineering.
Smart Images

Figure CN119080380B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of shield mud treatment, and in particular to a green and degradable mud flocculant and a preparation method thereof. Background Art
[0002] In recent years, with the rapid development of social economy and urbanization, slurry shield tunnel technology has become an indispensable key technology in the construction of major transportation infrastructure in my country. A large amount of waste mud will be generated during the slurry shield construction process. If the waste mud is not properly handled, it will not only cause serious pollution to the environment, but also affect the construction progress and safety.
[0003] Flocculants are key agents that can promote efficient sedimentation of suspended solids and reduce the efficiency of mud-water separation at the source. Their mechanisms of action include electrical neutralization, compression of the double electrical layer, adsorption bridging and net capture. The most widely used traditional flocculant is polyacrylamide (PAM for short). Although PAM can quickly condense suspended particles and improve mud-water separation efficiency during mud treatment, it has certain limitations. Existing PAM is difficult to completely degrade after use, and remains in the environment, causing secondary pollution problems. These residual substances may have long-term negative impacts on water bodies and soil, thereby threatening the health of the ecosystem and the quality of human life.
[0004] Chinese patent document CN109290064A discloses a method for preparing a graphene / titanium dioxide / polyacrylamide composite self-degradable flocculant, firstly preparing graphene oxide / titanium dioxide gel powder by sol-gel method, then heat treating the graphene oxide / titanium dioxide gel powder under inert atmosphere conditions to obtain graphene / titanium dioxide; placing an acetone-water solution of graphene / titanium dioxide and acrylamide in a quartz tube, irradiating with ultraviolet light, centrifuging, washing, and drying to obtain a graphene / titanium dioxide / polyacrylamide composite self-degradable flocculant. The flocculant of the present invention can overcome the characteristic that the polymer chain of polyacrylamide is easy to entangle, and form a comb-type structure on the surface of graphene / titanium dioxide, so that the polymer chain is better relaxed and the flocculation effect is good; it can be self-degraded under the condition of light. However, the graphene oxide and titanium dioxide uniform nanomaterials used in the invention have high surface energy and the defect of easy agglomeration, which in turn affects its flocculation effect. Summary of the invention
[0005] The main purpose of the invention is to provide a green and degradable mud flocculant, which has a good flocculation effect and can achieve the degradation of polyacrylamide under light conditions after use, thereby reducing environmental pollution.
[0006] To achieve the above purpose, the present invention provides a green and degradable mud flocculant, comprising the following components in parts by weight: 10-20 parts of polyacrylamide, 5-10 parts of photocatalytic degradation nanomaterials, 10-20 parts of anhydrous ethanol, 3-5 parts of modified graphene oxide, and 80-120 parts of water.
[0007] Preferably, the preparation method of the photocatalytic degradation nanomaterial is as follows:
[0008] S1: dispersing titanium dioxide powder and zinc oxide in an ethanol aqueous solution, adding vinyl trimethoxysilane, stirring and reacting at 40-60° C. for 2-4 h, filtering and drying to obtain a vinyl coupled nanomaterial;
[0009] S2: dispersing the vinyl coupling nanomaterial in acetone, adding 4-acetyl-2-allylphenol and acryloyloxyethyl trimethylammonium chloride, reacting at 60-80° C. for 4-6 hours under the action of an initiator, and cooling, filtering, washing and drying after the reaction to obtain a cationic nanomaterial;
[0010] S3: Add cationic nanomaterials and 1-aminoethyl-3-methylimidazolium bromide to water, adjust the pH value to 3-5, react at 50-70°C for 10-12h, and after the reaction is completed, cool to room temperature, collect the solids, wash and filter to obtain the photocatalytic degradation nanomaterials.
[0011] Preferably, in step (1), the ratio of titanium dioxide, zinc oxide and vinyltrimethoxysilane is 10-20:10-15:3-5.
[0012] Preferably, in step (2), the mass ratio of the vinyl coupling nanomaterial, 4-acetyl-2-allylphenol, and acryloyloxyethyltrimethylammonium chloride is 10-15:2-4:6-8.
[0013] Preferably, the initiator in step (2) is one of azobisisobutyronitrile and dibenzoyl peroxide.
[0014] Preferably, in step (3), the mass ratio of the cationic nanomaterial to 1-aminoethyl-3-methylimidazolium bromide is 5-8:1-2.
[0015] The photocatalytic degradation nano material of the invention first introduces vinyl groups on nano materials titanium dioxide and zinc oxide with photocatalytic degradation performance through vinyl trimethoxy silane, and then polymerizes with 4-acetyl-2-allylphenol and acryloyloxyethyl trimethyl ammonium chloride under the action of an initiator. On the one hand, cations can be introduced on the nano material to exert the performance of a cationic flocculant, and on the other hand, it can be convenient to react with ionic liquid 1-aminoethyl-3-methylimidazolium bromide in the subsequent reaction, which is conducive to the synergistic flocculation effect. By introducing cationic compounds and ionic liquids on the nano material, organic side chains are provided on the nano material molecules, so that the spatial structure of the nano material is expanded, thereby forming a network structure with multiple adsorption layers, and the network structure has better adsorption bridging performance, thereby improving the flocculation effect of the nano material. The photocatalytic material prepared by the invention has good dispersibility in a polyacrylamide solution and can well perform photocatalytic degradation on polyacrylamide.
[0016] Preferably, the modified graphene oxide is graphene oxide modified by a silane coupling agent; the silane coupling agent is one of KH550, KH560, and KH570; and the preparation method is as follows: dispersing graphene oxide in an ethanol aqueous solution, adding a silane coupling agent, stirring and reacting at 40-60° C. for 2-4 hours, filtering, collecting solids, and washing the solids with water, alcohol, and drying to obtain modified graphene oxide.
[0017] Preferably, the mass ratio of the graphene oxide to the silane coupling agent is 20-30:3-4.
[0018] The present invention also provides a method for preparing the above-mentioned green and degradable mud flocculant, comprising the following steps: weighing each raw material according to the formula, mixing the photocatalytic degradation nanomaterial, modified graphene oxide, anhydrous ethanol and water, and then ultrasonically treating the mixture, then adding polyacrylamide, heating and stirring the mixture to obtain the green and degradable mud flocculant.
[0019] Preferably, the ultrasonic conditions are 60-100 Hz, 120-150 W, and the ultrasonic time is 20-30 min.
[0020] Preferably, the heating temperature is 40-60° C. and the stirring time is 30-60 min.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention uses an organic flocculant in combination with an inorganic flocculant, which has a good flocculation effect on the shield mud. The flocculant can degrade polyacrylamide into small molecules such as CO2 and water that are harmless to the environment under light conditions, which is in line with the current trend of environmental protection and resource conservation; the present invention has a simple preparation process, low cost, and is easy to implement, and is suitable for being widely used in various slurry balance shield engineering projects;
[0023] 2. The present invention introduces acryloyloxyethyl trimethyl ammonium chloride cations into nanomaterials titanium dioxide and zinc oxide, so that the suspended particles in the mud lose stability, condense each other to enlarge the particles, form floccules, and improve the flocculation effect; then, the ionic liquid 1-aminoethyl-3-methylimidazolium bromide reacts with the phenolic hydroxyl group on 4-acetyl-2-allylphenol to obtain a photocatalytic degradation material with an organic branched chain structure, so that its spatial structure is expanded, thereby forming a network structure with multiple adsorption layers, and the network structure has better adsorption bridging performance, thereby improving the flocculation effect of the nanomaterial;
[0024] 3. The present invention avoids the agglomeration of graphene oxide and improves its dispersibility in polyacrylamide solution by adding modified graphene oxide. The graphene oxide itself has a large specific surface area and excellent surface properties, and can effectively adsorb suspended particles in the mud, thereby enhancing the flocculation effect; and its flaky structure can enhance the mechanical strength of the flocculant, so that it has better stability and durability in mud treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 This is a graph showing the results of sedimentation experiments of the green and degradable mud flocculants prepared in Examples 1-3 and Comparative Examples 1-2 of the present invention. DETAILED DESCRIPTION
[0027] To make the purpose, technical scheme and advantages of the embodiment of the present invention clearer, the technical scheme in the embodiment of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiment, it is carried out according to the normal conditions or the conditions recommended by the manufacturer. If the reagents or instruments used do not specify the manufacturer, they are all conventional products that can be purchased commercially. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes, taking "A and / or B" as an example, including scheme A, or scheme B, or schemes that A and B meet at the same time. In addition, the technical schemes between the various embodiments can be combined with each other, but must be based on the ability of ordinary technicians in the field to achieve. When the combination of technical solutions is contradictory or cannot be achieved, it should be considered that the combination of such technical solutions does not exist, and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present invention.
[0028] The sources of some raw materials used in the present invention are as follows:
[0029] Titanium dioxide, rutile type, with a particle size of 20 nm, was purchased from Qinghe Chaotai Metal Materials Co., Ltd.
[0030] Zinc oxide, content ≥99.99%, particle size 0.2-1.0μm, specific surface area 5-10g / m 2 , purchased from Hangzhou Jikang New Materials Co., Ltd.
[0031] Graphene oxide, with a content of 99%, a particle size of 0.5-3 μm, and a thickness of 0.55-1.2 nm, was purchased from Zhongke Leiming (Beijing) Technology Co., Ltd.
[0032] Polyacrylamide, anionic type, molecular weight of 12-20 million, solid content ≥90%, purchased from Foshan Jianghe Environmental Protection Chemical Co., Ltd.
[0033] Example 1
[0034] A method for preparing a green and degradable mud flocculant comprises the following steps: mixing 80g of photocatalytic degradation nanomaterial, 40g of modified graphene oxide, 150g of anhydrous ethanol and 1000g of water, ultrasonically treating the mixture for 25min at 80Hz and 135W, adding 150g of polyacrylamide, heating and stirring the mixture at 50°C for 40min to obtain the green and degradable mud flocculant.
[0035] The preparation method of the photocatalytic degradation nanomaterial is as follows:
[0036] S1: 15.4 g titanium dioxide powder and 12.3 g zinc oxide were dispersed in 500 mL 50 wt% ethanol aqueous solution, 4.6 g vinyl trimethoxy silane was added, and the mixture was stirred at 50 °C for 3 h, filtered, and dried to obtain a vinyl coupled nanomaterial;
[0037] S2: Disperse 14.8 g of vinyl coupled nanomaterial in 500 mL of acetone, add 2.6 g of dibenzoyl peroxide, and simultaneously drop 3.5 g of 4-acetyl-2-allylphenol and 6.7 g of acryloyloxyethyl trimethylammonium chloride at a rate of 2 drops / second. After the dropwise addition, react at 70°C for 5 h. After the reaction is completed, cool, filter, wash, and dry to obtain a cationic nanomaterial.
[0038] S3: Add 6.8g of cationic nanomaterial and 1.5g of 1-aminoethyl-3-methylimidazolium bromide to 200mL of water, adjust the pH value to 4 with 1mol / L hydrochloric acid aqueous solution, react at 60°C for 12h, and after the reaction is completed, cool to room temperature, collect the solid, wash and filter to obtain the photocatalytic degradation nanomaterial.
[0039] The preparation method of the modified graphene oxide is as follows: 25 g of graphene oxide is dispersed in 500 mL of 50 wt% ethanol aqueous solution, 3.3 g of silane coupling agent KH560 is added, and the mixture is stirred and reacted at 50° C. for 3 h, filtered, and solids are collected. The solids are washed with water, washed with alcohol, and dried to obtain modified graphene oxide.
[0040] The decomposition rate of polyacrylamide in the green and degradable mud flocculant tested using a photocatalytic degradation test device reached 85%.
[0041] Example 2
[0042] A method for preparing a green and degradable mud flocculant comprises the following steps: mixing 55g of photocatalytic degradation nanomaterial, 32g of modified graphene oxide, 108g of anhydrous ethanol and 800g of water, ultrasonically treating the mixture for 30min at 60Hz and 120W, adding 100g of polyacrylamide, heating and stirring the mixture at 40°C for 60min to obtain the green and degradable mud flocculant.
[0043] The preparation method of the photocatalytic degradation nanomaterial is as follows:
[0044] S1: 10.8 g titanium dioxide powder and 10.2 g zinc oxide were dispersed in 500 mL 50 wt% ethanol aqueous solution, 3.2 g vinyl trimethoxy silane was added, and the mixture was stirred at 40 °C for 4 h, filtered, and dried to obtain a vinyl coupled nanomaterial;
[0045] S2: Disperse 10.1 g of vinyl-coupled nanomaterial in 500 mL of acetone, add 2.2 g of dibenzoyl peroxide, and simultaneously drop 2.2 g of 4-acetyl-2-allylphenol and 6 g of acryloyloxyethyl trimethylammonium chloride at a rate of 2 drops / second. After the dropwise addition, react at 60°C for 8 h. After the reaction is completed, cool, filter, wash, and dry to obtain a cationic nanomaterial.
[0046] S3: Add 5.2g of cationic nanomaterial and 1.1g of 1-aminoethyl-3-methylimidazolium bromide to 200mL of water, adjust the pH value to 3 with 1mol / L hydrochloric acid aqueous solution, react at 50°C for 12h, and after the reaction is completed, cool to room temperature, collect the solid, wash and filter to obtain the photocatalytic degradation nanomaterial.
[0047] The preparation method of the modified graphene oxide is as follows: 20 g of graphene oxide is dispersed in 500 mL of 50 wt% ethanol aqueous solution, 3 g of silane coupling agent KH570 is added, the mixture is stirred and reacted at 40° C. for 4 h, and the solid is collected by filtering. The solid is washed with water, washed with alcohol, and dried to obtain the modified graphene oxide.
[0048] The decomposition rate of polyacrylamide in the green and degradable mud flocculant tested using a photocatalytic degradation test device reached 83%.
[0049] Example 3
[0050] A method for preparing a green and degradable mud flocculant comprises the following steps: mixing 100g of photocatalytic degradation nanomaterial, 50g of modified graphene oxide, 200g of anhydrous ethanol and 1200g of water, ultrasonically treating the mixture for 20min at 100Hz and 150W, adding 200g of polyacrylamide, heating and stirring the mixture at 60°C for 50min to obtain the green and degradable mud flocculant.
[0051] The preparation method of the photocatalytic degradation nanomaterial is as follows:
[0052] S1: 19.7 g titanium dioxide powder and 15 g zinc oxide were dispersed in 500 mL 50 wt% ethanol aqueous solution, 5 g vinyl trimethoxy silane was added, and the mixture was stirred at 60 °C for 4 h, filtered, and dried to obtain a vinyl coupled nanomaterial;
[0053] S2: Disperse 15 g of vinyl coupling nanomaterial in 500 mL of acetone, add 3 g of dibenzoyl peroxide, and simultaneously drop 4 g of 4-acetyl-2-allylphenol and 8 g of acryloyloxyethyl trimethylammonium chloride at a rate of 2 drops / second. After the dropwise addition, react at 80°C for 6 h. After the reaction is completed, cool, filter, wash, and dry to obtain a cationic nanomaterial.
[0054] S3: Add 8 g of cationic nanomaterial and 2 g of 1-aminoethyl-3-methylimidazolium bromide to 200 mL of water, adjust the pH value to 6 with 1 mol / L hydrochloric acid aqueous solution, react at 70°C for 12 h, and after the reaction is completed, cool to room temperature, collect the solid, wash and filter to obtain the photocatalytic degradation nanomaterial.
[0055] The preparation method of the modified graphene oxide is as follows: 30 g of graphene oxide is dispersed in 500 mL of 50 wt% ethanol aqueous solution, 4 g of silane coupling agent KH550 is added, and the mixture is stirred at 60° C. for 2 h, filtered, and solids are collected. The solids are washed with water, washed with alcohol, and dried to obtain modified graphene oxide.
[0056] The decomposition rate of polyacrylamide in the green and degradable mud flocculant tested using a photocatalytic degradation test device reached 82%.
[0057] Comparative Example 1
[0058] A method for preparing a green and degradable mud flocculant is similar to Example 1, except that no acryloyloxyethyltrimethylammonium chloride is added. The method specifically comprises the following steps: 80 g of photocatalytic degradation nanomaterial, 40 g of modified graphene oxide, 150 g of anhydrous ethanol and 1000 g of water are mixed, and then ultrasonically treated at 80 Hz and 135 W for 25 min, and then 150 g of polyacrylamide is added, and the mixture is heated and stirred at 50° C. for 40 min to obtain a green and degradable mud flocculant.
[0059] The preparation method of the photocatalytic degradation nanomaterial is as follows:
[0060] S1: 15.4 g titanium dioxide powder and 12.3 g zinc oxide were dispersed in 500 mL 50 wt% ethanol aqueous solution, 4.6 g vinyl trimethoxy silane was added, and the mixture was stirred at 50 °C for 3 h, filtered, and dried to obtain a vinyl coupled nanomaterial;
[0061] S2: Disperse 14.8 g of vinyl coupling nanomaterial in 500 mL of acetone, add 2.6 g of dibenzoyl peroxide, and drop 3.5 g of 4-acetyl-2-allylphenol at a rate of 2 drops / second. After the dropwise addition, react at 70° C. for 5 h. After the reaction is completed, cool, filter, wash, and dry to obtain the modified nanomaterial;
[0062] S3: Add 6.8g of modified nanomaterial and 1.5g of 1-aminoethyl-3-methylimidazolium bromide to 200mL of water, adjust the pH value to 4 with 1mol / L hydrochloric acid aqueous solution, react at 60°C for 12h, and after the reaction is completed, cool to room temperature, collect the solid, wash and filter to obtain the photocatalytic degradation nanomaterial.
[0063] The preparation method of the modified graphene oxide is as follows: 25 g of graphene oxide is dispersed in 500 mL of 50 wt% ethanol aqueous solution, 3.3 g of silane coupling agent KH560 is added, and the mixture is stirred and reacted at 50° C. for 3 h, filtered, and solids are collected. The solids are washed with water, washed with alcohol, and dried to obtain modified graphene oxide.
[0064] Comparative Example 2
[0065] A method for preparing a green and degradable mud flocculant is similar to Example 1, except that 1-aminoethyl-3-methylimidazolium bromide is not added. The method specifically comprises the following steps: 80 g of photocatalytic degradation nanomaterial, 40 g of modified graphene oxide, 150 g of anhydrous ethanol, and 1000 g of water are mixed, and then ultrasonically treated at 80 Hz and 135 W for 25 min, and then 150 g of polyacrylamide is added, and the mixture is heated and stirred at 50° C. for 40 min to obtain a green and degradable mud flocculant.
[0066] The preparation method of the photocatalytic degradation nanomaterial is as follows:
[0067] S1: 15.4 g titanium dioxide powder and 12.3 g zinc oxide were dispersed in 500 mL 50 wt% ethanol aqueous solution, 4.6 g vinyl trimethoxy silane was added, and the mixture was stirred at 50 °C for 3 h, filtered, and dried to obtain a vinyl coupled nanomaterial;
[0068] S2: Disperse 14.8 g of vinyl-coupled nanomaterial in 500 mL of acetone, add 2.6 g of dibenzoyl peroxide, and simultaneously add 3.5 g of 4-acetyl-2-allylphenol and 6.7 g of acryloyloxyethyltrimethylammonium chloride at a rate of 2 drops / second. After the addition is completed, react at 70°C for 5 hours. After the reaction is completed, cool, filter, wash, and dry to obtain the photocatalytic degradation nanomaterial.
[0069] The preparation method of the modified graphene oxide is as follows: 25 g of graphene oxide is dispersed in 500 mL of 50 wt% ethanol aqueous solution, 3.3 g of silane coupling agent KH560 is added, and the mixture is stirred and reacted at 50° C. for 3 h, filtered, and solids are collected. The solids are washed with water, washed with alcohol, and dried to obtain modified graphene oxide.
[0070] Test Case
[0071] 1. Sedimentation test:
[0072] 65% of the silty soft soil was added with water to prepare a slurry with a water content of 200%. Then 80 mL was poured into a 100 mL graduated cylinder for standby use. 20 mL of the green and degradable mud flocculants prepared in Examples 1-3 and Comparative Examples 1-2 were added to the prepared mud and stirred at a rate of 80 r / min for 5 minutes to allow the flocculants to fully react with the soil particles to form agglomerates. After that, the size of the mud agglomerates in the mixed solution and their sedimentation were observed, and the sinking scale of the flocculated agglomerates in the graduated cylinder was recorded. The experimental results are shown in FIG. Figure 1 shown.
[0073] 2. Add equal amounts of the green and degradable mud flocculants prepared in Examples 1-3 of the present invention and Comparative Examples 1-2 to a feed barrel containing shield mud, with an amount of 200 g / L of flocculant; stir for 20 min and let stand for 2 h, and transport the mud to a sludge dewatering centrifuge through a diaphragm pump. Adjust the speed of the mud dewatering centrifuge to 3000 r / min. After centrifugation for 5 min, measure the filtrate turbidity, total phosphorus, total nitrogen, COD value and filter cake moisture content, and calculate the turbidity removal rate;
[0074] Turbidity removal rate = [(shield slurry turbidity - filtrate turbidity) / shield slurry turbidity] × 100%
[0075] The representative pollutant content and water content of shield mud are shown in Table 1 below:
[0076] Table 1: Representative contaminant content and water content of shield mud
[0077]
[0078] The test results are shown in Table 2:
[0079] Table 2 Flocculation test results of green and biodegradable mud flocculants
[0080]
[0081] It can be seen from Table 1 above that the flocculant in the present invention has an excellent deturbidity effect on shield mud and greatly reduces the water content of the mud cake. The flocculant also has a strong adsorption capacity for pollutants in water.
[0082] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A green and degradable mud flocculant, characterized in that: The invention comprises the following components in parts by weight: 10-20 parts of polyacrylamide, 5-10 parts of photocatalytic degradation nanomaterials, 10-20 parts of anhydrous ethanol, 3-5 parts of modified graphene oxide, and 80-120 parts of water; The preparation method of the photocatalytic degradation nanomaterial is as follows: S1: dispersing titanium dioxide powder and zinc oxide in an ethanol aqueous solution, adding vinyl trimethoxysilane, stirring and reacting at 40-60° C. for 2-4 h, filtering and drying to obtain a vinyl coupled nanomaterial; S2: dispersing the vinyl coupling nanomaterial in acetone, adding 4-acetyl-2-allylphenol and acryloyloxyethyl trimethylammonium chloride, reacting at 60-80° C. for 4-6 hours under the action of an initiator, and cooling, filtering, washing and drying after the reaction to obtain a cationic nanomaterial; S3: Add cationic nanomaterials and 1-aminoethyl-3-methylimidazolium bromide to water, adjust the pH value to 3-5, react at 50-70°C for 10-12h, and after the reaction is completed, cool to room temperature, collect the solids, wash and filter to obtain the photocatalytic degradation nanomaterials.
2. The mud flocculant according to claim 1, characterized in that: In the step S1, the ratio of titanium dioxide, zinc oxide and vinyltrimethoxysilane is 10-20:10-15:3-5.
3. The mud flocculant according to claim 1, characterized in that: In the step S2, the mass ratio of the vinyl coupling nanomaterial, 4-acetyl-2-allylphenol, and acryloyloxyethyltrimethylammonium chloride is 10-15:2-4:6-8.
4. The mud flocculant according to claim 1, characterized in that: In step S2, the initiator is one of azobisisobutyronitrile and dibenzoyl peroxide.
5. The mud flocculant according to claim 1, characterized in that: In the step S3, the mass ratio of the cationic nanomaterial to 1-aminoethyl-3-methylimidazolium bromide is 5-8:1-2.
6. The mud flocculant according to claim 1, characterized in that: The modified graphene oxide is graphene oxide modified by a silane coupling agent.
7. The mud flocculant according to claim 6, characterized in that: The silane coupling agent is one of KH550, KH560 and KH570.
8. The mud flocculant according to claim 6, characterized in that: The preparation method of the modified graphene oxide is as follows: dispersing graphene oxide in an ethanol aqueous solution, adding a silane coupling agent, stirring and reacting at 40-60° C. for 2-4 hours, filtering, collecting solids, and washing the solids with water, alcohol, and drying to obtain modified graphene oxide.
9. A method for preparing the mud flocculant according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: weighing various raw materials according to a formula, mixing photocatalytic degradation nanomaterials, modified graphene oxide, anhydrous ethanol and water, performing ultrasonic treatment, adding polyacrylamide, heating and stirring the mixture to obtain a green and degradable mud flocculant.
Citation Information
Patent Citations
Preparation method of graphene / titanium dioxide / polyacrylamide composite self-degradation flocculating agent
CN109290064A
Method for cooperative treatment hard-degraded organic wastewater by using polyacrylamide flocculation catalyst
CN104609595A
Degradable polyacrylamide oil displacement agent and preparation method thereof
CN105778878A